Natural Feed Additives Modulate Immunity and Mitigate Infection with Sphaerospora molnari (Myxozoa:Cnidaria) in Common Carp: A Pilot Study - Ganeva, Vyara O; Korytář, Tomáš; Pecková, Hana; McGurk, Charles; Mullins, Julia; Yanes-Roca, Carlos; Gela, David; Lepič, Pavel; Policar, Tomáš; Holzer, Astrid S (Pathogens (Basel, Switzerland), 2020)
Myxozoans are a diverse group of cnidarian parasites, including important pathogens in different aquaculture species, without effective legalized treatments for fish destined for human consumption. We tested the effect of natural feed additives on immune parameters of common carp and in the course of a controlled laboratory infection with the myxozoan Sphaerospora molnari. Carp were fed a base diet enriched with 0.5% curcumin or 0.12% of a multi-strain yeast fraction, before intraperitoneal injection with blood stages of S. molnari. We demonstrate the impact of these treatments on respiratory burst, phagocytosis, nitric oxide production, adaptive IgM+ B cell responses, S. molnari-specific antibody titers, and on parasite numbers. Both experimental diets enriched B cell populations prior to infection and postponed initial parasite proliferation in the blood. Curcumin-fed fish showed a decrease in reactive oxygen species, nitric oxide production and B cell density at late-stage infection, likely due to its anti-inflammatory properties, favoring parasite propagation. In contrast, multi-strain yeast fraction (MsYF)-fed fish harbored the highest S. molnari-specific antibody titer, in combination with the overall lowest parasite numbers. The results demonstrate that yeast products can be highly beneficial for the outcome of myxozoan infections and could be used as effective feed additives in aquaculture.
Keywords: innate immunity; adaptive immunity; parasite; in-feed; yeast; fish; curcumin